Upaya Meningkatkan Hasil Belajar IPA dengan Menerapkan Model Word Square Berbantuan Media Papan Lembar Balik pada Peserta Didik Kelas V SDN 3 Palangka Tahun Pelajaran 2016/2017: Efforts to Improve Science Learning Outcomes by Applying the Word Square Model Assisted by Flip Sheet Media in Class V Students of SDN 3 Palangka 2016/2017 Academic Year - Sarda Sari; Suniati Suniati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to: (1) Describe the science learning activities of the fifth grade students of Palangkaraya SDN-3 in the 2016/2017 Academic Year on the application of the Word Square model Assisted by Media Flip Sheets, (2) Improve science learning outcomes of fifth grade students of SDN-3 Palangka 2016/2017 Academic Year after the application of the Word Square model Assisted by Flip Sheet Media. The type of research used by researchers is Class Action Research (PTK) with research subjects of all fifth-grade students in Palangka Elementary School-3 totaling 32 students. Data collection techniques in this study used observation and tests. Data analysis using qualitative, quantitative data analysis and Mixed Methods. The results of this study indicate that: (1) Activity of fifth grade students of Palangka Elementary School-3 in the 2016/2017 school year in science learning after applying the Word Square learning model Assisted by the Flip Sheet Media Board to be very good, because students are active, enthusiastic, listen to explanations teacher and enthusiastic in following the learning process. The results of the observations of teacher activities on teaching and learning activities carried out by observer I and observer II during the learning process of science in the first cycle average aspects of teacher activity 3.9 in the outstanding category and the universal element of students is 3.67 in the group very good. (2) There is an increase in science learning outcomes by applying the Word Square learning model Assisted Media Flip Sheet Board in class V science subjects at Palangka Elementary School-3 in the academic year 2016/2017. This is indicated by the learning outcomes seen through the class average in the first cycle which is equal to 84.22 and the completeness percentage of students in classical is 100%, from the predetermined provisions namely for KKM of 65 and completeness criteria in traditional 85%. With this, it can be concluded that there is an increase in science learning outcomes after applying the Word Square learning model assisted by the Flip Sheet Media Board.